Human circulating bacteria and dysbiosis in non-infectious diseases - Goraya, Mohsan Ullah; Li, Rui; Mannan, Abdul; Gu, Liming; Deng, Huixiong; Wang, Gefei (Frontiers in Cellular and Infection Microbiology, 2022)
Blood microorganisms were once thought to indicate infection. Blood in healthy people appears to be devoid of growing bacteria; nonetheless, intracellular dormant forms of bacteria have been reported previously. With breakthroughs in sequencing and bioinformatics, the presence of bacterial DNA in healthy human blood initiated the controversy of human blood microbiota (HBM). Recently, bacteria-specific DNA and culturable bacteria were found in healthy human blood. Researchers wanted to study the phenomena of a “healthy blood microbiota” by providing a thorough description of bacterially produced nucleic acids using many complementing molecular and traditional microbiological approaches. Because blood is a relatively limited and particular environment, culturability and plate count issues can be overcome using enhanced cultured procedures. However, more evidence is required to confirm that healthy human blood contains normal microbiota. Cavities, mouth and intestinal microbiota, trauma, surgery, and animal/insect bites can introduce bacteria into human blood. All these factors strengthen the concept of transient blood bacteria too. The presence of blood bacteria may be caused by temporary immunological clearance and absorption by dendritic or M cells. This review provides an extensive and comprehensive analysis that suggests that healthy blood bacteria may not be typical microbiota but transient circulatory microorganisms. In this study, we look at how contaminants (Escherichia, Shigella, Pseudomonads, etc.) from the skin, laboratory environments, and reagents can affect the interpretation of blood-derived microbial information and the relationship between the circulating bacteria and non-communicable diseases. Circulating transient bacteria may play a role in the pathogenesis of non-infectious diseases such as diabetes and CVD. Contamination-free hematological studies can aid in understanding the disease mechanisms, therapy, and biomarkers.